Family Support on Anxiety Level of Chronic Kidney Failure Patients during Hemodialysis at Padang City Hospital, West Sumatra - Putri, Cindy Claudya; Oresti, Syalvia; Mailita, Weni (STIKes Alifah Padang, 2023)
Patients who are completely dependent on hemodialysis may experience anxiety. It was discovered that patients with End Stage Renal Disease exhibited anxiety to depression (57.3% )(Damanik, 2020). The patient's anxiety will have an impact on the hemodialysis intervention process in order to avoid this, it is vital to research elements that can alleviate anxiety, one of which is family support. The goal of this study was to see if there was a link between family support and anxiety levels in patients with chronic kidney failure during hemodialysis at Padang City Hospital in West Sumatra. A quantitative cross-sectional design was adopted in the investigation. The study was carried out at Padang City Hospital in West Sumatra. This study included 172 chronic kidney failure patients who had hemodialysis from November to January 2023. Purposive sampling was used, with a total sample size of 115 persons. A questionnaire was used to collect data. The data was analyzed using univariate and bivariate methods. According to the findings of the study, the highest level of anxiety was in the category of moderate anxiety (46.1%), followed by a lack of family support (56.5%). Following the Pearson Chi-Square statistical test, it yielded a p-value of 0.000 (p-value 0.05). This study revealed that there is a link between family support and anxiety levels in patients with chronic kidney failure having hemodialysis at Padang City Hospital in West Sumatra. It is expected that nurses will involve the family in the treatment process and meet spiritual requirements as a key factor in minimizing patient anxiety.